A 22 yr Cycle of the Network Topology of Solar Active Regions - Eduardo Flández; Alejandro Zamorano; Víctor Muñoz (The Astrophysical Journal)
In this paper, solar cycles 21–24 were compared using complex network analysis. A network was constructed for these four solar cycles to facilitate the comparison. In these networks, the nodes represent the active regions of the Sun that emit flares, and the connections correspond to the sequence of solar flares over time. This resulted in a directed network with self-connections allowed. The model proposed by Abe and Suzuki for earthquake networks was followed. The incoming degree for each node was calculated, and the degree distribution was analyzed. It was found that for each solar cycle, the degree distribution follows a power law, indicating that solar flares tend to appear in correlated active zones rather than being evenly distributed. Additionally, a variation in the characteristic exponent γ for each cycle was observed, with higher values in even cycles compared to odd cycles. A more detailed analysis was performed by constructing 11 yr networks and shifting them in 1 yr intervals. This revealed that the characteristic exponent shows a period of approximately 22 yr coincident with the Hale cycle, suggesting that the complex networks provide information about the solar magnetic activity.